An Introduction to the legal system of The United States - FRANSWORTH, E Allan (Oxford & IBH Publishing, 2010)
In the updated, fourth edition of this classic text which has been translated into over a dozen languages, constitutional scholar and Columbia Law School professor E. Allan Farnsworth provides a clear explanation of the structure and function of the U.S. legal system in one handy reference. An Introduction to the Legal System of the United States, Fourth Edition is designed to be a general introduction to the structure and function of the legal system of the United States, and is especially useful for those readers who lack familiarity with fundamental establishments and practices.